Natural history of glaucomatous optic neuropathy in highly myopic Chinese: study protocol for a registry cohort study. Issue 12 (30th December 2020) - Song, Yunhe; Wang, Wei; Lin, Fengbin; Chen, Shida; Jin, Ling; Li, Fei; Gao, Kai; Cheng, Weijing; Xiong, Jian; Zhou, Rouxi; Chen, Meiling; Liang, Jiaen; et al.
Abstract : Introduction: Myopic maculopathy and glaucoma belong to the most common causes of irreversible blindness worldwide and, having an ocular axial elongation as one of their main risk factors, can occur together. The detection of glaucomatous optic neuropathy (GON) in highly myopic eyes is clinically and technically difficult, and there is no information available, neither about the natural course of GON or about the course of GON under intraocular pressure-lowering therapy. We therefore designed this study to explore the natural course of GON in highly myopic eyes. Methods and analysis: In this single-centred longitudinal registry cohort study, 813 highly myopic individuals will be recruited and undergo detailed ophthalmic examinations. High myopia is defined by a myopic refractive error of ≥−6 D or an axial length of ≥26.5 mm. GON is defined by a glaucomatous appearance of the optic nerve head or glaucomatous visual field (VF) defects. GON progression is defined by either change of the optic disc or VF. Ethics and dissemination: Ethical approval has been obtained from the ethical committee of the Zhongshan Ophthalmic Center (ZOC), Sun Yat-sen University, China (ID: 2019KYPJ079). All the participants are required to provide informed consents. Results will be disseminated through scientific meetings and published in peer-reviewed journals. The data will be deposited at the clinical research centre in ZOC using electronic data capture system, and a copy of paper files will also be kept. Only members of the project team will have access to these data. Trial registration number: NCT04302220 .